1998
DOI: 10.1243/1350650981542173
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis for the influence of water film on adhesion between rail and wheel

Abstract: The adhesion force between rail and wheel is one of the important factors for proceeding towards the realization of high-speed railway. On the other hand, it is supposed that the water film formed between the rail and wheel has a remarkable influence on the adhesion force under rainy condition at higher speeds. In this paper, taking Bett and Cappi's viscosity values of water, which show quite a different behaviour from the viscosity of oil, the influence has been investigated of important factors such as rolli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…These two fluid film thickness values have been estimated using the regression equations of Dowson and Higginson [13] for oil and Chen et al [14] for water. The results are shown in Table 4.…”
Section: Fluid Film Thicknessmentioning
confidence: 99%
“…These two fluid film thickness values have been estimated using the regression equations of Dowson and Higginson [13] for oil and Chen et al [14] for water. The results are shown in Table 4.…”
Section: Fluid Film Thicknessmentioning
confidence: 99%
“…During the first stage it propagates through the surface deformation zone (about 10 µm deep). Then the crack turns downwards by a further [25][26][27][28][29][30][31][32][33][34][35] o and grows to a depth of around 300-400 µm . The branches of crack appear to grow at around 90 o to the main crack.…”
Section: Water Lubricationmentioning
confidence: 99%
“…Chen et. al [25] have developed a similar approach based on numerical results with low viscosity fluid lubricants: …”
Section: Fluid Film Thicknessmentioning
confidence: 99%
“…Their experimental results showed a similar tendency to those that described in references [2] and [3] regarding the effect of rolling speed on the adhesion coefficient, and indicated that heavy axle loads gave slightly higher adhesion coefficients. Chen et al [1,5] simulated the adhesion coefficient between wheel and rail by applying elasto-hydrodynamic lubrication (EHL) and rough surfaces contact theory. Not only the rolling speed, the water temperature, asperity height and asperity profile of surfaces also had significantly effects on the adhesion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…To verify the effects of water temperature on the adhesion coefficient obtained by theoretical investigation in references [1] and [5], a number of experiments have been conducted on a twin disc rolling contact machine under wet conditions at different water temperatures. The water temperature has been clarified to have a significant effect on the adhesion coefficient by the experiments, which is qualitatively consistent to the theoretical results.…”
Section: Introductionmentioning
confidence: 99%